Developing people's information capabilities fostering information literacy in educational, workplace and community contexts - Hepworth, Mark, 1955-; Walton, Geoff (Library and information science (New York, N.Y.), 2013)
Developing people's information capabilities : fostering information literacy in educational, workplace and community contexts is Vol 8 of the well regarded Library and Information Science Series. This book hones in on accessible issues across different work and educational contexts and is of value to both academic and practitioner.